Unusual presentations of late onset diaphragmatic hernia: a six year study - Aggarwal, Sumeet; Aggarwal, Amika; Ded, K. S. (International Surgery Journal, 2017)
Background: Late-presenting congenital diaphragmatic hernia (CDH) is a rare subset of CDH, most of the information is derived from small series or case reports. The aim of this study is to document the varied presentations of late-presenting CDH in a tertiary hospital. Methods: Information about late-presenting CDH (diagnosed at later than 30 days of age) was identified from the data collected by a 5 year reterospective study and 1 year prospective study. Results: Twenty five cases were studied over a period of 6 years with 5 years of reterospective study and 1 year of prospective study. Three cases had a morgagni hernia (2 right-sided, 1 central, 2 males and 1 female). There were 16 males (64%) and 9 females (36%). Major associated anomalies were identified in 6 cases (24%). Cardiac anomalies included ventricular septal defect (n = 4), atrial septal defect (n = 2), gastroesophageal reflux was found in 3 cases, 1 of which required surgery. Presenting symptoms were respiratory in 8 (32%), gastrointestinal in 13 (52%), both in 4 (16%). The hernia was left-sided in 17 (68%), right-sided in 5 (20%), and central 3 (12%). Patients with gastrointestinal symptoms invariably had left-sided hernias (n = 10), whereas patients with respiratory symptoms (n = 8) seemed equally likely to have right- or left-sided lesions. A primary repair without patch was done in all cases with 100% survival. Conclusions: Presenting symptoms of late-onset CDH can be respiratory or gastrointestinal, but presentation with gastrointestinal problems was more common in left-sided hernias, whereas respiratory symptoms were seen with equal preponderance in left and right-sided lesions. The prognosis is excellent once the correct diagnosis is made.